Age-associated changes of the intrinsic nervous system in relation with interstitial cells in the pre-weaning goat rumen - Liang, Yu (Aging (Albany NY), 2019)
In this study, we investigated the neural changes and their relationships with interstitial cells (ICs) in the rumen of pre-weaning goats by transmission electron microscopy, western blot and immunofluorescence (antibody: general neuronal marker-Protein Gene Product (PGP9.5)/ IC marker-vimentin). The immunofluorescence results showed that PGP9.5-positive reaction was widely distributed in neuronal soma (NS) and nerve fibre (NF). The NSs were observed in the ganglia of the myenteric plexus (MP) but not in the submucosal plexus. The mean optical density (MOD) of the whole of PGP9.5-positive nerves and the protein expression level of PGP.5 in the rumen wall both decreased significantly with age. However an obvious increase MOD of PGP.5-positive NFs within the rumen epithelium were observed. In the MP, the nerves and ICs were interwoven to form two complex networks that gradually tightened with age. Furthermore, NSs and nerve trunks were surrounded by a ring-boundary layer consisting of several ICs that became physically closer with aging. Moreover, ICs were located nearby NFs within the ML, forming connections between ICs, smooth muscle cells and axons. This study describes the pattern of neural distribution and its association with ICs in the developing rumen which shed light on the postpartum development of ruminants.